Evaluation of phenylethylamine type entactogens and their metabolites relevant to ecotoxicology – a QSAR study - Takač Milena Jadrijević-Mladar; Magina Joao Daniel Casimiro; Takač Tin (Acta Pharmaceutica)
The impact of the selected entactogens and their o-quinone metabolites on the environment was explored in QSAR studies by the use of predicted molecular descriptors, ADMET properties and environmental toxicity parameters, i.e., acute toxicity in Tetrahymena pyriformis (TOX_ATTP) expressed as Th_pyr_pIGC50/mmol L−1, acute toxicity in Pimephales promelas, the fathead minnow (TOX_FHM) expressed as Minnow LC50/mg L−1, the acute toxicity in Daphnia magna (TOX_DM) expressed as Daphnia LC50/mg L−1 and bioconcentration factor (BCF).